Preparation method of sulfonate ligand modified perovskite quantum dots
By using octylamine methane sulfonate as a multi-ligand passivator, the problem of easy formation of vacancy defects in perovskite quantum dots during the synthesis process is solved, and a more uniform particle size and higher perovskite quantum dots are achieved. luminous performance and stability.
Patent Information
- Application Number
- CN202411201202.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-29
AI Technical Summary
Perovskite quantum dots are prone to form halide vacancy defects during the synthesis and purification process, resulting in agglomeration and settlement, reducing luminescence performance and stability.
Octylamine methane sulfonate is used as a multi-ligand passivator. Through the joint action of octylamine and methylsulfonic acid, the uncoordinated lead ions and bromide ions of perovskite quantum dots are efficiently passivated and the ligands are enhanced with The combination of quantum dots improves stability and luminescence properties.
It effectively reduces the vacancy defects caused by the increase in surface area due to size reduction during the quantum dot synthesis process, making the particle size of perovskite quantum dots more uniform, with better conductivity, and improved luminescence performance and stability.
Smart Images

Figure CN119331595A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite quantum dots and relates to a method for preparing perovskite quantum dots modified with sulfonate ligands. Background Art
[0002] Quantum dots are small particles with a size of 2-10nm made of semiconductor materials. The radius of quantum dots is less than or close to the Bohr radius, so they have a quantum confinement effect, which limits the transport properties of carriers and affects the band structure of quantum dots. It is precisely because of this band structure that is different from conventional bulk materials and the adjustability of the band structure with size that quantum dot materials have significant advantages in the field of photoelectric luminescence, such as high luminescence efficiency, good luminescence quality, and adjustable luminescence spectrum. As a semiconductor material, all-inorganic perovskite quantum dots have the characteristics of simple synthesis, narrow emission peak (half-maximum width of 12-42nm), high fluorescence quantum efficiency (up to 90%), etc., and have bright application prospects in the fields of light-emitting diodes, solar cells, photodetectors, lasers and bioimaging. However, due to the unique ionic crystal structure, large surface area, weak bond strength of lead halide, and highly dynamic binding of ligands to the surface of perovskite quantum dots, halide vacancy defects are easily formed during the synthesis and purification process. This will lead to the agglomeration and sedimentation of perovskite quantum dots, thereby reducing the luminescence performance and stability.
[0003] Improving the stability and luminescence performance of perovskite nanocrystals by surface treatment is a common and efficient material modification method. For the traditional oleic acid / oleylamine (OA / OLA) binary ligand system, reversible proton transfer is easy to occur between ligands, coupled with the weak binding effect of surface ligands, resulting in a large amount of surface ligand shedding and surface vacancy defects during purification and placement, which are the main reasons affecting the stability and luminescence performance of perovskite quantum dots.
[0004] CN 116804151 A discloses a blue light emitting perovskite quantum dot and its preparation method and application. The preparation method can effectively fill the vacancies generated by the lack of lead in the synthesis process by doping a specific amount of germanium ions in the CsPbBr3 perovskite quantum dot. However, it does not focus on the stability of the perovskite quantum dot. Therefore, it is very necessary to seek a suitable surface ligand to passivate the surface of the quantum dot. Summary of the invention
[0005] In order to solve the above problems in the prior art, the purpose of the present invention is to provide a method for preparing sulfonate ligand-modified perovskite quantum dots.
[0006] Another object of the present invention is to provide a sulfonate ligand-modified perovskite quantum dot.
[0007] Another object of the present invention is to provide a sulfonate ligand-modified perovskite quantum dot for use in a light-emitting material or a perovskite solar cell.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing sulfonate ligand-modified perovskite quantum dots comprises the following steps:
[0010] S1: mixing a cesium source, octadecene and oleic acid, drying under vacuum, introducing an inert gas and heating to obtain a first mixed solution;
[0011] S2: Lead bromide, octadecene, oleylamine, oleic acid and octylamine methyl sulfonate are mixed, vacuum dried, the first mixed solution is added under inert gas, the reaction is quenched, and the solution of perovskite quantum dots modified with the sulfonate ligand is obtained.
[0012] The invention adopts multi-ligand passivation in the process of preparing quantum dots. Octylamine and methanesulfonic acid in octylamine methanesulfonate jointly replace oleylamine and oleic acid, effectively passivate the uncoordinated lead ions and bromide ions of perovskite quantum dots, and improve the luminescence performance and stability of quantum dots. Since the insulating effect of the short-chain organic ligand octylamine is weaker than that of the long-chain oleylamine, and the confinement effect of octylamine on quantum dots is more obvious, the perovskite quantum dots obtained by the invention are smaller and more uniform in size, and have better conductive properties. Methanesulfonic acid can activate the ligand, strengthen the binding effect between the ligand and the quantum dots, and thus improve the stability of the quantum dots.
[0013] Octylamine and methanesulfonic acid need to be added to the reaction system as a whole in one step, which can reduce the time the quantum dots are corroded by the outside world. If they are added in steps, there will be uneven binding of the ligands and the perovskite quantum dots, which will affect the crystallization of the perovskite quantum dots, making the particle size of the quantum dots uneven, thereby reducing the crystallinity and stability of the quantum dots.
[0014] The octylamine methyl sulfonate ligand added in the process of preparing CsPbBr3 perovskite quantum dots in the present invention can strengthen the combination of surface ligands and quantum dots during the crystallization process, which is beneficial to reduce the defects caused by ligand shedding during the purification process, thereby improving the luminescence performance.
[0015] Sudden cooling can quickly reduce the growth rate of quantum dots and control the particle size of quantum dots. If the quantum dots are allowed to cool naturally, their particle size will be too large.
[0016] Specifically, the molar ratio of lead bromide to octylamine methanesulfonate is (0.8-1.1): (0.5-2).
[0017] Too little octylamine methyl sulfonate will cause some lead ions to be unable to bond with halogens, forming vacancies and reducing the stability of perovskite quantum dots. Too much octylamine methyl sulfonate will cause the quantum dots to be separated by a large number of ligands, hindering the carrier transmission between quantum dots and reducing the luminescence performance of quantum dots.
[0018] Specifically, in step S1, the molar ratio of the cesium source, octadecene and oleic acid is 1:6:(1-3).
[0019] As a non-coordinating solvent, octadecene can dilute the ligand, reduce the viscosity of the system, and make the material concentration in the reaction system uniform.
[0020] Specifically, the inert gas in steps S1 and S2 is at least one of nitrogen, helium and argon.
[0021] Specifically, the cesium source in step S1 is cesium carbonate.
[0022] Specifically, ventilation is required before vacuum drying in step S1, and the specific ventilation steps include: introducing inert gas after vacuuming, and repeating it more than four times.
[0023] Specifically, the vacuum drying temperature in step S1 is 90° C. to 130° C., and the vacuum drying time is 1 to 2 hours.
[0024] Specifically, the heating temperature in step S1 is 140°C to 160°C.
[0025] Specifically, in step S1, the solution needs to be heated until it is completely clarified.
[0026] Specifically, the first mixed solution in step S1 needs to be kept warm at 90-110° C. for later use.
[0027] Specifically, in step S2, the molar ratio of lead bromide, octadecene, oleylamine, oleic acid and octylamine methanesulfonate is (0.8-1.1): (60-64): (20-23): (20-24): (0.5-2).
[0028] More specifically, in step S2, the molar ratio of lead bromide, octadecene, oleylamine, oleic acid and octylamine methanesulfonate is (0.9-1): (60-64): (20-23): (20-24): (0.5-2).
[0029] It should be noted that the main component of the first mixed solution is cesium oleate.
[0030] Specifically, the molar ratio of cesium oleate to lead bromide in the first mixed solution in step S2 is 1:(2-3).
[0031] Specifically, the vacuum drying temperature in step S2 is 140° C. to 160° C., and the vacuum drying time is 0.5 h to 1.5 h.
[0032] The purpose of vacuum drying in steps S1 and S2 is to remove moisture from the air and the reaction solution, which is beneficial to reduce moisture erosion during the preparation of quantum dots.
[0033] Specifically, the reaction temperature in step S2 is 110°C to 140°C.
[0034] Specifically, the reaction time in step S2 is 20s to 40s.
[0035] Specifically, the quenching treatment in step S2 refers to placing the reaction container in an ice-water mixture for cooling.
[0036] Specifically, the quenching temperature in step S2 is 0°C to 4°C.
[0037] Specifically, the quenching time in step S2 is 15s to 25s.
[0038] Specifically, the specific steps of purification in step S2 include: mixing the quenched mixed solution with ethyl acetate and centrifuging for the first time, dispersing the separated precipitate in the dispersion, adding ethyl acetate, centrifuging again, and dispersing the obtained precipitate in the dispersion again to obtain the solution of the sulfonate ligand-modified perovskite quantum dots.
[0039] More specifically, the dispersion liquid is n-hexane.
[0040] More specifically, the rotation speed of the initial centrifugation is 7000-9000 rpm, and the time of the initial centrifugation is 15-25 min.
[0041] More specifically, the speed of the second centrifugation is 4000-6000 rpm, and the time of the second centrifugation is 5-15 min.
[0042] The present invention also protects a sulfonate ligand-modified perovskite quantum dot prepared by the above method.
[0043] The present invention also protects the use of sulfonate ligand-modified perovskite quantum dots in luminescent materials or perovskite solar cells.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The present invention adopts octylamine methane sulfonate to passivate the perovskite quantum dots, which effectively reduces the vacancy defects caused by the increase of surface area due to size reduction in the quantum dot synthesis process, strengthens the binding between the ligand and the quantum dots, makes the particle size of the quantum dots more uniform, and further improves the luminescence performance and stability of the perovskite quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Graphs showing the fluorescence emission spectra of quantum dots prepared in the examples and comparative examples of the present invention.
[0047] Figure 2 TEM images of quantum dots prepared in the examples and comparative examples of the present invention.
[0048] Figure 3 This is a wetting angle test diagram of the CsPbBr3 blue light quantum dots prepared in Example 3 of the present invention and Comparative Example 1.
[0049] Figure 4 The particle size distribution diagram of quantum dots prepared in the examples and comparative examples of the present invention.
[0050] Figure 5 This is a graph showing the luminescence performance of Example 3 and Comparative Example 1 in water. DETAILED DESCRIPTION
[0051] The present invention is further described below in conjunction with embodiments and comparative examples, which are only intended to better illustrate the present invention rather than to limit it. The enumerated embodiments are only preferred embodiments, not all. Changes, substitutions, modifications, etc. made by those skilled in the art without making creative work all belong to the protection scope of the present invention.
[0052] If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0053] Example 1
[0054] S1. Mix 0.825g of Cs2CO3, 3.5mL of oleic acid and 9.6mL of octadecene to obtain a mixed solution. Add the mixed solution into a 100mL three-necked flask and ventilate the three-necked flask more than four times (vacuum and pass argon). Then place the three-necked flask in a heating mantle and heat it to 110°C in a vacuum and dry it for 1.5h. Then pass argon and heat it to 150°C until the solution is completely clear, thus obtaining a cesium oleate precursor solution. Keep it warm at 100°C for standby use.
[0055] S2.1 Add 0.35g PbBr2, 20mL octadecene, 0.12g octylamine methanesulfonate, 7mL oleic acid and 7mL oleylamine to a three-necked flask, ventilate the three-necked flask more than four times (vacuum and pass argon), and then dry it in a vacuum at 150°C for 1h. Then, pass argon and cool to 125°C. Then, quickly inject 1mL of cesium oleate precursor solution, react for 30s, and quickly immerse the three-necked flask containing the product solution system in ice water for quenching for 20s to obtain a crude solution of CsPbBr3 quantum dots.
[0056] S2.3 Ethyl acetate and CsPbBr3 perovskite quantum dot crude solution were mixed in a volume ratio of 3:1, and then centrifuged at 8000 rpm for 20 minutes. The precipitate was collected and redispersed in 3 mL of hexane, and then 20 mL of ethyl acetate was added, and the precipitate was collected by centrifugation at 5000 rpm for 10 minutes, and redispersed in 5 mL of anhydrous hexane for later use.
[0057] Example 2
[0058] In this example, sulfonate ligand-modified perovskite quantum dots were prepared according to the steps of Example 1, except that 0.22 g of octylamine methanesulfonate was added in step S2.1; the other steps remained unchanged.
[0059] Example 3
[0060] In this example, sulfonate ligand-modified perovskite quantum dots were prepared according to the steps of Example 1, except that 0.32 g of octylamine methanesulfonate was added in step S2.1; the other steps remained unchanged.
[0061] Example 4
[0062] In this example, sulfonate ligand-modified perovskite quantum dots were prepared according to the steps of Example 1, except that 0.43 g of octylamine methanesulfonate was added in step S2.1; the other steps remained unchanged.
[0063] Comparative Example 1
[0064] In this example, sulfonate ligand-modified perovskite quantum dots were prepared according to the steps of Example 1, except that octylamine methyl sulfonate was not added in step S2.1; the other steps remained unchanged.
[0065] Performance Testing
[0066] The fluorescence emission spectra of the embodiment and the comparative example were tested using a HORIBA Fluorolog-3 fluorescence spectrophotometer. Light with a wavelength of 365 nm was used as the excitation light source. Before the test, the CsPbBr3 solution was diluted with dimethylformamide (DMF), and then the diluted solution was dripped into a cuvette.
[0067] The TEM images of the embodiment and the comparative example were obtained by a FEI Talos F200s microscope. Before observing the morphology of the test sample, the sample was appropriately diluted with dimethylformamide (DMF), and then the diluted solution was dropped onto the carbon mesh for testing. When the solvent on the carbon mesh was completely evaporated, the test could be carried out.
[0068] The wetting angle images of the examples and comparative examples were obtained by a pco.dimax HS high-speed camera. The sample was appropriately diluted with dimethylformamide (DMF), and then the diluted solution was dropped onto the test platform, and the image when the droplet was in a stable state was taken as the test result.
[0069] The fluorescence emission spectra of the embodiments and comparative examples are shown in FIG. Figure 1 As shown. As can be seen from the figure, the wavelength corresponding to the luminescence peak is 480nm~510nm, and the prepared perovskite quantum dots emit blue light. The luminescence intensity of the CsPbBr3 quantum dots treated with octylamine methyl sulfonate is higher than that of the original untreated quantum dots, and the luminescence peak is shifted to varying degrees. The occurrence of this phenomenon can be attributed to the passivation of the octahedral defects of the perovskite by octylamine methyl sulfonate, which increases the probability of radiative recombination of carriers. At the same time, due to the partial substitution of oleylamine by octylamine methyl sulfonate, the coupling between the grains in the perovskite is enhanced, resulting in a certain red shift in the peak position. In addition, it can also be seen that the half-peak width of the luminescence peak of the crystal treated with octylamine methyl sulfonate is smaller than that of the original CsPbBr3 quantum dots in Comparative Example 1. This means that the grain size inside the perovskite treated with octylamine methyl sulfonate is more uniform, giving the quantum dots a higher color purity.
[0070] TEM images of the embodiments and comparative examples are shown in FIG. Figure 2 As shown. By observing the morphology of CsPbBr3 quantum dots passivated with different contents of octylamine methyl sulfonate by TEM, it can be seen that the original unpassivated CsPbBr3 and the octylamine methyl sulfonate passivated CsPbBr3 quantum dots in Comparative Example 1 have good monodispersity and a complete cubic structure, and as the amount of octylamine methyl sulfonate added increases, the gaps between the individual quantum dots become more obvious. This is because octylamine methyl sulfonate has a certain steric hindrance and can effectively passivate the surface of the quantum dots. At the same time, it can be seen that the quantum dots in Examples 3 and 4 show good crystallinity, and no obvious grain aggregation phenomenon is found. This can be attributed to the fact that the strong binding energy between the short-chain octylamine methyl sulfonate and the quantum dots enhances the stability of the grains.
[0071] The hydrophobic angles of Example 3 and Comparative Example 1 were tested by wetting angle test. It was found that the hydrophobic angle of the perovskite quantum dots in Example 3 was 89.9°, which was significantly higher than the hydrophobic angle of 40.7° of the perovskite quantum dots in Comparative Example 1. This is due to the fact that octylamine methyl sulfonate can provide greater steric hindrance for CsPbBr3 quantum dots compared to oleylamine, effectively reducing the erosion of water on the inside of the perovskite.
[0072] The particle size histograms of the embodiments and comparative examples are shown in FIG. Figure 4As shown. The size of CsPbBr3 nanocrystals introduced with octylamine methyl sulfonate is mostly about 4.5nm, showing a more uniform size distribution compared to unpassivated nanocrystals. However, due to the excessive addition of octylamine methyl sulfonate, it can be found that the perovskites treated with octylamine methyl sulfonate all have larger grains. In Example 4, there are more agglomerated grains with a size of 6.5nm. This means that as the amount of octylamine methyl sulfonate added increases, more oleic acid and oleylamine are replaced, the coupling force between each grain is enhanced, and the size of the nanocrystals agglomerates and becomes larger.
[0073] Figure 5 The figure is a graph of the luminescence performance of Example 3 and Comparative Example 1 in water. The figure intuitively shows that Example 3 can still emit bright sky blue light even when placed in water and irradiated by an excitation light source, while the CsPbBr3 nanocrystalline quantum dots in Comparative Example 1 have been decomposed in water and cannot exist in the form of a film on the glass sheet. After the original film structure is destroyed, the quantum dots cannot continue to aggregate and disperse into the water, making the water turbid, and cannot stably emit color under the irradiation of the excitation light source.
[0074] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing sulfonate ligand-modified perovskite quantum dots, characterized in that: The following steps are involved: S1: mixing a cesium source, octadecene and oleic acid, drying under vacuum, introducing an inert gas and heating to obtain a first mixed solution; S2: Lead bromide, octadecene, oleylamine, oleic acid and octylamine methyl sulfonate are mixed, vacuum dried, heated under inert gas, and then the first mixed solution is added, and the mixture is quenched after the reaction and purified to obtain a solution of perovskite quantum dots modified with the sulfonate ligand.
2. The perovskite quantum dots modified with sulfonate ligands according to claim 1, characterized in that: The molar ratio of lead bromide to octylamine methanesulfonate is (0.8-1.1): (0.5-2).
3. The method for preparing sulfonate ligand-modified perovskite quantum dots according to claim 1, characterized in that: In the step S1, the molar ratio of the cesium source, octadecene and oleic acid is 1:6:(1-3).
4. The method for preparing sulfonate ligand-modified perovskite quantum dots according to claim 1, characterized in that: In the step S2, the molar ratio of lead bromide, octadecene, oleylamine, oleic acid and octylamine methanesulfonate is (0.8-1.1): (60-64): (20-23): (20-24): (0.5-2).
5. The method for preparing sulfonate ligand-modified perovskite quantum dots according to claim 1, characterized in that: The main component of the first mixed solution is cesium oleate. In step S2, the molar ratio of cesium oleate to lead bromide in the first mixed solution is 1:(2-3).
6. The method for preparing sulfonate ligand-modified perovskite quantum dots according to claim 1, characterized in that: The heating temperature in step S1 is 140°C to 160°C.
7. The method for preparing sulfonate ligand-modified perovskite quantum dots according to claim 1, characterized in that: The reaction temperature in step S2 is 110° C. to 140° C., and the reaction time is 20 s to 40 s.
8. The method for preparing sulfonate ligand-modified perovskite quantum dots according to claim 1, characterized in that: The quenching temperature in step S2 is 0°C to 4°C, and the quenching time is 15s to 25s.
9. A sulfonate ligand-modified perovskite quantum dot prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the sulfonate ligand-modified perovskite quantum dots according to claim 9 in light-emitting materials or perovskite solar cells.
Citation Information
Patent Citations
Preparation method of perovskite quantum dots
CN107500345A
Ligand adjustment-based perovskite quantum dot stability increasing method
CN109370566A
Method for preparing efficient and stable inorganic perovskite quantum dots by using double-layer ligand
CN112175613A
Surface-treated perovskite nanocrystal as well as preparation method and application thereof
CN115197692A
Blue light emitting perovskite quantum dot and preparation method and application thereof
CN116804151A